PENGARUH ENDORPHINE MASSAGE TERHADAP SKALA INTENSITAS NYERI PADA IBU BERSALIN NORMAL PRIMIPARA INPARTU KALA I DI PMB KOTA BENGKULU TAHUN 2020 - Savitri, Wewet; Yulyana, Nispi; Maulidyanti, Anisah Tifani (Poltekkes Kemenkes Medan, 2021)
Pain in labor is a manifestation of uterine contractions in the first stage of labor that can cause fatigue so that it causes a decrease in uterine contractions. Many methods are offered to reduce pain during labor, non pharmacologically including endorphine massage has been proven to increase the ability of mothers to tolerate pain during childbirth. The purpose of this study was to determine the effect of endorphine massage on pain intensity scale in first-time normal mothers in PMB Bengkulu City in 2020. This study used quasi-experimental designs with the pretest-posttest Non Equivalent Control Group. The intervention group the endorphine massage was given to first stage mothers, while the control group was given deep breath relaxation techniques. Total sample are 30 people, divided into 2 groups, each each of which amounted to 15 people. The statistical analysis used was the Wilcoxon test and the Mann-Whitney Test. The results of thetest Wilcoxon showed that the average value of pain intensity in the first stage before and after the intervention was 7.53 and it became 6.00 with a p-value = 0.000 (<0.05). whereas in the control group the average value was 7.20 and after being treated it became 6.00 with a p-value = 0.001 (<0.05) which means that there was an influence of endorphine massage on the intensity scale of pain in first-time normal primipara delivery mothers in PMB Bengkulu City. It is expected that midwives can pay more attention to maternal needs for comfort by applying endorphine massage in the control of labor pain. Keywords:Labor, Labor Pain, Endorphine Massage